Methodological approach for the development of terminology subsets ICNP®: an integrative review - Jorge Wilker Bezerra Clares; Maria Célia de Freitas; Maria Vilaní Cavalcante Guedes
Objective To analyze the methodological aspects used for the preparation of terminology subsets of the International Classification for Nursing Practice (ICNP®), in dissertations and theses in the Brazilian nursing. Method This is an integrative review of the Brazilian dissertations and theses defended in the period from 2007 to 2013, which were included seven dissertations. Results The increasing production of studies on the theme by Brazilian nurses shows a concern for a unified language for the profession. However, the results demonstrate the lack of uniformity in the conduct of studies, especially in relation to the stages of content validation. The initiatives of some authors to systematize alternative methods for creating these subsets also stood out. Conclusion We suggest the development of new terminology subsets, following standards of methodological rigor, as well as its application and validation by the selected clientele, to ensure greater reliability of results and desired changes for the profession.